2016
DOI: 10.1038/srep36302
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Environmental Factors on Bacterial Communities within the Rhizosphere of the Cu-tolerant plant, Elsholtzia splendens

Abstract: Bacterial communities of rhizospheric soils play an important role in the tolerance and uptake of metal-tolerant/hyperaccumulating plants to metals, e.g. the Cu-tolerant Elsholtzia splendens native to China. In this work, pyrosequencing of the bacterial 16S rRNA gene was firstly applied to investigate the rhizospheric bacterial community of E. splendens grown at Cu contaminated sites. The 47 phyla including 11 dominant phyla (>1%) in E. splendens rhizosphere were presented. The effects of Cu and other environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 61 publications
4
25
1
Order By: Relevance
“…Many other studies (Chodak et al 2013, Jiang et al 2016, Yun et al 2017) have concluded the same, determining pH directly influences bacterial metabolism, growth, and reproduction (Rousk et al 2010, Lachaud 2011; pH also changes the physical and chemical properties of sediment, contributing to further changes in bacterial community structure and diversity. Many other studies (Chodak et al 2013, Jiang et al 2016, Yun et al 2017) have concluded the same, determining pH directly influences bacterial metabolism, growth, and reproduction (Rousk et al 2010, Lachaud 2011; pH also changes the physical and chemical properties of sediment, contributing to further changes in bacterial community structure and diversity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many other studies (Chodak et al 2013, Jiang et al 2016, Yun et al 2017) have concluded the same, determining pH directly influences bacterial metabolism, growth, and reproduction (Rousk et al 2010, Lachaud 2011; pH also changes the physical and chemical properties of sediment, contributing to further changes in bacterial community structure and diversity. Many other studies (Chodak et al 2013, Jiang et al 2016, Yun et al 2017) have concluded the same, determining pH directly influences bacterial metabolism, growth, and reproduction (Rousk et al 2010, Lachaud 2011; pH also changes the physical and chemical properties of sediment, contributing to further changes in bacterial community structure and diversity.…”
Section: Discussionmentioning
confidence: 95%
“…Of environmental factors, pH had the most significant effect on bacterial community structure. Many other studies (Chodak et al 2013, Jiang et al 2016, Yun et al 2017) have concluded the same, determining pH directly influences bacterial metabolism, growth, and reproduction (Rousk et al 2010, Lachaud 2011; pH also changes the physical and chemical properties of sediment, contributing to further changes in bacterial community structure and diversity. Conversely, pH had little impact on fungal community structure.…”
Section: Discussionmentioning
confidence: 95%
“…The function prediction analysis of PICRUSt based on high-throughput sequencing has been applied in analyzing the ecological function of different plants [67,68]. We hypothesized that changes in the bacterial community structure would elicit a functional response.…”
Section: Discussionmentioning
confidence: 99%
“…This method is convenient, fast, and cheap, and its prediction results have high reliability [20][21][22][23]. PICRUSt has been used to study the function of soil bacteria associated with different plants, such as barley, tomato [24], Suaeda salsa [25], Sedum alfredii [26], and Elsholtzia splendens [27], laying the foundation for further investigations of the ecological functions of bacteria in these habitats.…”
Section: Introductionmentioning
confidence: 99%